3D self-assembled VS4 microspheres with high pseudocapacitance as highly efficient anodes for Na-ion batteries. Issue 46 (11th October 2018) - Li, Wenbin; Huang, Jianfeng; Feng, Liangliang; Cao, Liyun; He, Shuwei
Abstract : The decreasing crystallinity of VS4 microspheres greatly increases the surface active sites, and then promotes the pseudocapacitive behavior, and finally leads to the high capacity, long cycling life and high rate capability. Abstract : Surface structure plays a decisive role in the surface capacity and electrochemical kinetics of rechargeable batteries. Tuning the surface structure of building blocks has been considered to be a new effective strategy to promote the electrochemical performance of 3D self-assembled nanoarchitectures. Herein, VS4 microspheres assembled from the nano-units with different crystallinities are synthesized via a facile template-free hydrothermal method. The results show that the electrochemical performance of VS4 microspheres as anode materials for sodium-ion batteries (SIBs) largely depends on their crystallinity, and a VS4 electrode with the lowest crystallinity delivers a high reversible capacity of 412 mA h g −1 at 0.2 A g −1 after 230 cycles and that of 345 and 293 mA h g −1 even at 1.0 and 2.0 A g −1, respectively. The insertion mechanism is revealed within the selected voltage window of 0.50–3.00 V. Further analysis suggests that decreasing the crystallinity of the nano-units can dramatically enhance the pseudocapacitive behavior of VS4 microspheres, which takes the main responsibility for the improvement of sodium storage properties. This work can provide a new insight for the exploration and design of high-performance anodes for SIBs.